2010
DOI: 10.1017/s1744552310000066
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gate: family lawyers as gatekeepers to a holistic service

Abstract: In 2001, the Legal Services Commission (LSC) introduced a new pilot, the Family Advice and Information Network (FAInS), which recognised that family law clients typically face a cluster of legal and non-legal issues. Family lawyers involved in FAInS were encouraged to address a client’s legal problems, and then refer the client to other services for assistance with non-legal issues. In this way, family law clients were to be offered a holistic service, with the lawyer acting as a ‘case manager’ who helped matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One approach would be to identify the most appropriate gatekeeper that could refer clients to the most appropriate legal and non-legal systems. Melville and Laing (2010) have shown how family lawyers, despite their awareness of the clients' cross-legal and non-legal problems, and their specific training in directing clients to other legal or non-legal assistance, still avoided referring them to other services and generally found it difficult to place non-legal issues within a legal framework. Without abandoning the multi-agency approach Melville and Laing, however, concluded that lawyers may not be the most suitable gatekeeper of different legal and non-legal support services.…”
Section: New Legal Aid Initiative: Cross-functional Mentors Pre-and Pmentioning
confidence: 99%
“…One approach would be to identify the most appropriate gatekeeper that could refer clients to the most appropriate legal and non-legal systems. Melville and Laing (2010) have shown how family lawyers, despite their awareness of the clients' cross-legal and non-legal problems, and their specific training in directing clients to other legal or non-legal assistance, still avoided referring them to other services and generally found it difficult to place non-legal issues within a legal framework. Without abandoning the multi-agency approach Melville and Laing, however, concluded that lawyers may not be the most suitable gatekeeper of different legal and non-legal support services.…”
Section: New Legal Aid Initiative: Cross-functional Mentors Pre-and Pmentioning
confidence: 99%
“…Lawyers have been shown to restrict the engagement of clients to the provision of factual information, limit discussion to a narrow focus on legal issues, only involve clients in decision-making when it is absolutely necessary, and present a limited range of options (e.g. Blumberg, 1967;Skolnick, 1967;Rosenthal, 1974;Hosticka, 1979;Bogoch & Danet, 1984;Simon, 1988;Mather et al, 1995;McConville & Mirsky, 1995;Pepper, 1995;Michelson, 2006;Kozin, 2007;Melville & Laing, 2008, 2010.…”
Section: Introductionmentioning
confidence: 99%